2015
DOI: 10.31384/jisrmsse/2015.13.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization on Economic Growth: Four Sector Analysis in Case of Pakistan

Abstract: The study analyses the impact of urbanization on economic growth of Pakistan from 1975-2012. Conceptual framework of the present theory is based on the theory of Lewis (1954) and Tadaro (1976). Co-integration analysis is used to examine the impact of urbanization on economic growth of four sectors namely agriculture, manufacturing, industrial and services sector of the economy. Results show that urbanization affect economic growth significantly and they have a long run relationship. It was found that urbanizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Cities are the regions of modern living, where a greater number of educated and skilled women join the workforce. To have better employment opportunities and higher gains, urbanization is considered as a rational decision of investing human capital (Nasir & Naz, 2015). The overall world's energy use has become more than twice in last ).…”
Section: Figure-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Cities are the regions of modern living, where a greater number of educated and skilled women join the workforce. To have better employment opportunities and higher gains, urbanization is considered as a rational decision of investing human capital (Nasir & Naz, 2015). The overall world's energy use has become more than twice in last ).…”
Section: Figure-1mentioning
confidence: 99%
“…The rapid growth of population, unemployment, transportation, and rapidly growing industries causes urbanization. (Nasir & Naz, 2015) concluded that urbanization is a key determinant of economic growth of industrial, services and manufacturing sectors of the economy. According to (Lucas, 2004), urban agglomeration leads to higher and efficient productivity due to knowledge spillover.…”
Section: Literature Reviewmentioning
confidence: 99%